Long Non-coding RNA MALAT1 as a Novel Diagnostic Biomarker of Coronary Artery Disease in Type 2 Diabetes Mellitus: A Comprehensive Review - Nearmeen M.Rashad , Amal Saeed El-Shal, Ahmad Atef Zaki Arafa,Esraa Samy Ahmed, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Background: Coronary artery disease (CAD) remains a major cause of morbidity and mortality among patients withtype 2 diabetes mellitus (T2DM). The coexistence of T2DM accelerates atherosclerosis and vascular inflammationnthrough hyperglycemia